IMPLEMENTASI NILAI SUNNAH NABI PADA ANAK-ANAK DI TADIKA RAUDHAH BARA’QINUL EIMAN (RBE) PRESCHOOL, PENANG, MALAYSIA - Puspita Sari, Dila; Munawir Pasaribu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study investigates how young children at Tadika Raudhah Bara'qinul Eiman (RBE) Preschool in Penang, Malaysia, use the principles of the Prophet's Sunnah. In August 2025, semi-structured teacher interviews, participant observation, and documentation analysis were used to gather data using a qualitative descriptive technique. The results show that through habituation, role modeling, and organized play-based activities, fundamental Sunnah values such as eating and drinking while seated, using courteous expressions (such as